ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL BILANGAN RIIL - Martin, Sri Novia; Gusteti, Meria Ultra (STKIP Andi Matappa, 2020)
Real Analysis is a compulsory subject for students in the 5th semester of the Mathematics education study program at STKIP Adzkia. This study aims to determine the learning difficulties experienced by students of STKIP Adzkia in riil number courses. This research was qualitative research. The research subjects were students of Mathematics STKIP Adzkia 5th semester study program. Data were obtained from observations and tests. The steps of ata analysis techniques were Â data reduction, data presentation, and conclusion drawing. Difficulties experienced by students could be seen from the mistakes made by students when solving riil number problems. The results of this study indicated that the difficulties experienced by students in the material of riil numbers were (1) difficulties in applying the concept; (2) Difficulties in developing concepts that have already been learned; (3) difficulty in performing arithmetic operations; (4) difficulty in using certain procedures; (5) difficulty in constructing ideas or ideas to prove a Mathematical statement.This indicates that there are many difficulties in learning real analysis.